عالقة التفكك األسري بإنحراف األحداث دراسة ميدانية في مؤسسة إصالح األحداث بمدينة أربيل - Zana Ahmed Perdawod (QALAAI ZANIST JOURNAL, 2019)
The study aims to investigate the extent to which the phenomenon of family disintegration contributes to juvenile delinquency; through it to identify the following sub-goals: the level of separation and divorce among the parents of the research units, poor relations between the parents, the absence of one or both parents due to death, imprisonment or emigration ,criminal precedents of Parents or siblings, the economic circumstances of juvenile families, the type of pedagogy, socialization, the parent’s dealingwith juveniles, and the relationship of all metioned subject with juvenile delinquency. The study was based on the descriptive and comparative approach through comprehensive social survey method as a general method of research, and the data was collected by questinnaire. The sample was drawnfrom the prisoners in the juvenile reform institution in the city of Erbil. The total number of research units (68) of those sentenced in the institution.The study found several results, the most important of which are: The physical disintegration of family because of the absence of one or both parents as a result of death, abandonment or polygamy is one of the main causes of different types of juvenile delinquency.Likewise,the moral disintegration of the family is accoutned as one of the factors of juvenile delinquencydue to poor social relationships between the parents, or because of continuous differences and quarrels between them, or existing someone who has criminal record or drinks alcohol inside family, or following the wrong method of upbringing and socialinzing of children to prevent them from excessive or cruel treatment or discrimination, andfinally not monitoring childern outside the house by parents. The presence of disability or chronic disease by one or both parents is considered one of the reasons behind family disintegration and juvenile delinquency in the city of Erbil. key concepts: Juvenile, Juvenile Delinquency, Family Distingration.